Penerapan Extreme Programming (XP) Dalam Website Sistem Informasi Desa Bersinar (Bersih Narkoba) di Kabupaten Tulungagung - Mochamad Affan Sabilla Firdos; Taufiq Agung Cahyono; Mohamad Khoirul Ansor (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
The Prevention, Eradication, Abuse, and Illicit Trafficking of Narcotics (P4GN) program through the BERSINAR Village in Tulungagung Regency still faces problems in the dissemination of information that tends to be conventional, unintegrated, and difficult for the public to access widely. This condition has an impact on the low reach of information, minimal public understanding, and limited public participation in supporting the P4GN program. This study aims to develop a BERSINAR Village information system website that functions as an integrated medium for delivering program information, a means of policy socialization, and public education regarding the dangers of narcotics and prevention efforts. The website development was carried out using the Extreme Programming (XP) method which includes the stages of planning, design, coding, and testing, with an emphasis on user involvement in each stage of development. System requirements data were collected through observation and interviews with relevant parties, then analyzed to determine the system's features and functionality. System testing was carried out using black box testing to ensure all functions run according to requirements. The results of the study indicate that the developed website is able to support more effective information delivery and has the potential to increase community participation in the BERSINAR Village program.